The effect of wet-salting preservation method on the physicochemical and microbial quality of Dasyatis sp. - Novianti Adi Rohmanna; Zuliyan Agus Nur Muchlis Majid; Syifa’ Rabbani; Sri Kumalaningsih; Sucipto Sucipto (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2021)
Microbial Dasyatis sp. (stingray fish) was a popular fish in Indonesia. Commonly, this fish is processed into smoked fish and perishable products. Therefore, it needs a preservation method through the handling process. Wet salting was considered as an efficient and inexpensive preservation method. This study aimed to determine the effect of brine concentration on the physicochemical and microbial quality of Dasyatis sp. The research used a Completely Randomized Design with factor of brine concentration (i.e. 10%, 20% and 30%). The statistical analysis consists of variance analysis (ANOVA) and followed by LSD or DMRT test (α=5%). The fish sample was soaked in brine solution at different concentrations for one hour. Total crude protein, physicochemical (total volatile basic nitrogen/TVB-N, tri-methyl amine/TMA, and pH), and (total plate count/TPC) were analyzed. The results showed that the brine concentration effect of physicochemical and microbiological of Dasyatis sp (p<0.05). The best treatment was obtained at the application of 10% brine concentration, which had physicochemical parameters as follows: 6.92 pH, 6.110 mgN/100g TVB-N, 5.520 mgN/100g TMA, 16.78 % protein, and 0.537x105 CFU/ml TPC.